Modeling hydroprene effects on eggs and 5th instar wandering phase larvae of the indianmeal moth, Plodia interpunctella (Lepidoptera:Pyralidae) - Mohandass, Sivakumar (Kansas State University, 2005)
The control of Indianmeal moth [Plodia interpunctella (Hübner)], a commonly found serious stored product pest around the world, relies mainly upon chemical control methods. Because of recent changes in the laws and regulations governing pesticide usage in the United States, there is an increasing need for finding safer chemicals to control insect pests. Hydroprene, an insect growth regulator, is considered to be a safe alternative. In this study, I quantified the effects of hydroprene on two critical life stages of Indianmeal moth, the eggs and 5th instar wandering phase larvae. Maximum development time in the untreated controls was 13.6 ± 0.6 d at 16°C and minimum development time was 2.3 ± 0.4 d at 32°C. At 20°C and 24°C, the effect of hydroprene on egg development became more evident; development time generally increased with exposure interval, with some variability in the data. The mean egg mortality among all temperatures was 7.3 ± 4.6%. Among the treatments, mortality of eggs increased as the exposure periods increased within any given temperature, with a dramatic increase in mortality with increase in temperature. Egg mortality was lowest at 16°C when exposed for 1 h (0 ± 3%), but mortality gradually increased up to 32 ± 3% when exposed for 18 h. Within each exposure interval, there was a direct increase in mortality as the temperatures increased. For the 5th instar wandering phase larvae, the longest development time among the treatments of 47.2 ± 1.3 d occurred at 16ºC when the larvae were exposed for 30 h, whereas the shortest development time of 7.0 ± 0.5 d occurred when the larvae were exposed for 1 h at 32ºC. Among treatments, the greatest larval mortality (82.0 ± 0.1%) occurred when larvae were exposed for 30 h at 28ºC, while the minimum mortality of 0.0 ± 0.5% occurred at 16ºC when larvae were exposed for 1 h. Response-surface models derived from this study can be used in simulation models to estimate the potential consequences of hydroprene on Indianmeal moth population dynamics.
Keywords: Hydroprene; Indianmeal moth; Egg; Wandering phase larvae; Modeling; Biology, Entomology (0353)